An industrial application: improving performance of an old forging press - GENÇ, GARİP (My University, 2022)
Forging is one of the most important production methods in applications where the disadvantages of machining are not desired. However, the possibility of micro-cracking in the material at the end of the forging process should be considered. The main constraints here are the aging of hydraulic systems and possible casting defects. Therefore, in this study, the modernized process of an old forging press with a capacity of 30000 kN was carried out. For this purpose, the capacity of the forging press has been increased by modifying a new generation pump and hydraulic accumulator group. Thus, by increasing the cycle time of the hydraulic forging press, it is known that effective forging can be performed in a shorter time (from 1.7 to 1.3 seconds). When the modernization results are examined, it is seen that the necessary forging processes can be completed before the material cools down to the critical temperature.
Keywords: Tarımsal Bilimler; Ziraat; Tarım Makineleri; Tarım Alet ve Makineleri; Mühendislik ve Teknoloji; Agricultural Sciences; Agriculture; Farm Machinery; Agricultural Tools and Machines; Engineering and Technology; MÜHENDİSLİK, MEKANİK; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); ENGINEERING, MECHANICAL; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Makine Mühendisliği; Hesaplamalı Mekanik; Otomotiv Mühendisliği; Mühendislik (çeşitli); Fizik Bilimleri; General Engineering; Mechanical Engineering; Computational Mechanics; Automotive Engineering; Engineering (miscellaneous); Physical Sciences; open die forging; hydraulic forging press; fast forging; energy recovery; SYSTEM; DESIGN; open die forging; hydraulic forging press; fast forging; energy recovery